Association between metabolic dysfunction associated steatotic liver disease and gallstones in the US population using propensity score matching - Yingying Zhang; Jingjing Zhang; Dan Yu; Fan Tu; Jun Liu; Bing Han; Binghua Li; Yihang Yuan; Chaobo Chen; Mingli Zhou (Scientific Reports, 2025)
Abstract The novel diagnostic term Metabolic Dysfunction-Associated Steatotic Liver Disease (MASLD) requires at least one cardiovascular risk factor for diagnosis. While the relationship between gallstones and Non-Alcoholic Fatty Liver Disease (NAFLD) has been debated, the association between MASLD and gallstones remains unclear. This cross-sectional study aimed to explore this relationship using National Health and Nutrition Examination Survey (NHANES) data from 2017 to 2020. Participants were stratified into two groups based on MASLD diagnosis, and propensity score matching (PSM) was employed to reduce biases. Of 15,560 participants, 7922 met the inclusion criteria, with 2697 (34.0%) diagnosed with MASLD. Gallstone prevalence was higher in the MASLD group (14.2%) compared to the non-MASLD group (8.5%). After PSM, 4536 participants were analyzed, revealing a significant association between MASLD and gallstones (OR = 1.30, 95% CI 1.09–1.56, P = 0.003). This association remained robust across crude and adjusted analyses, with subgroup and sensitivity analyses further supporting the findings. In conclusion, MASLD is significantly associated with an increased risk of gallstones in the US population. These findings highlight the need to consider this relationship in clinical strategies for prevention and management of gallstone disease.